2005
DOI: 10.1007/s00431-005-0001-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequential cardiac troponin T following delivery and its relationship with myocardial performance in neonates with respiratory distress syndrome

Abstract: We measured serial cardiac troponin T in babies with respiratory distress syndrome and in "healthy" controls (no cardiorespiratory support required). We investigated relationships between cardiac troponin T and myocardial performance in respiratory distress syndrome. This was a prospective observational study at a large tertiary maternity unit that recruited 104 "healthy" babies from whom individual samples were collected. A further 24 infants with respiratory distress syndrome and 14 "healthy" preterm infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 25 publications
5
25
3
3
Order By: Relevance
“…No significant correlation was found between cTnT concentrations and gestational age, which is consistent with most literature data [10,11,12,16]. On the other hand, research by Awada et al [14], including 116 healthy newborns on the 1st day of life, revealed a significant correlation between these parameters - the highest cTnT was found in preterm newborns.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…No significant correlation was found between cTnT concentrations and gestational age, which is consistent with most literature data [10,11,12,16]. On the other hand, research by Awada et al [14], including 116 healthy newborns on the 1st day of life, revealed a significant correlation between these parameters - the highest cTnT was found in preterm newborns.…”
Section: Discussionsupporting
confidence: 81%
“…Previously performed studies revealed an increase of troponin level right after birth and maintenance of elevated concentration (comparing to adults) to the 7th or (according to other authors) 15th day of life [11,15]. In the current literature there were no studies found evaluating cTnT in infants over 2 weeks of age.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…1 Infants requiring inotropes had higher cTnT compared to those who were normotensive but this did not reach statistical significance possibly due to the relatively small number of subjects. Clark SJ et al 18,22 showed a similar effect of inotropes on cTnT levels. Whether the rise in cTnT in hypotensive infants is a direct result of the inotropes or cardiovascular compromise occurring before delivery is unclear.…”
Section: Biochemical Markers and Preterm Infants A El-khuffash Et Almentioning
confidence: 86%
“…9 cTnT levels are higher in premature infants with respiratory distress syndrome (RDS). 10 Biochemical markers of impaired function and ischemic damage may serve as an important screening tool in centers where echocardiography resources are limited. We hypothesized that NTpBNP and cTnT are good markers of myocardial function in preterm infants.…”
Section: Introductionmentioning
confidence: 99%